Pirates of the Mediterranean: An empirical investigation of bargaining with asymmetric information - Attila Ambrus; Eric Chaney; Igor Salitskiy (Quantitative Economics, 2018)
We investigate the effect of delay on prices in bargaining situations using a data set containing thousands of captives ransomed from Barbary pirates between 1575 and 1692. Plausibly exogenous variation in the delay in ransoming provides ev- idence that negotiating delays decreased the size of ransom payments, and that much of the effect stems from the signalling value of strategic delay, in accordance with theoretical predictions. We also structurally estimate a version of the screen- ing type bargaining model, adjusted to our context, and find that the model fits both the observed prices and acceptance probabilities well.
Keywords: D23; K42; N45; 330; Bargaining; piracy; ransom